School Leaders’ Experiences on Dealing with Students Exposed to Domestic Violence - Berger, Emily (Journal of family violence, 2022)
School leaders’ experiences and perceptions of students’ domestic violence experiences and trauma-informed school interventions have been overlooked. This semi-structured qualitative study aimed to investigate three areas regarding school leaders’ perceptions regarding domestic violence-exposed students: 1) the experiences of school leaders in dealing with these students; 2) the barriers and strengths associated with managing these students; and 3) school leaders’ recommendations for overcoming any barriers related to this issue in schools. Interviews conducted with 15 school leaders were analysed using thematic analysis. School leaders were found to be instrumental in influencing school culture and support systems surrounding students’ exposure to domestic violence. However, school leaders provided mixed reports regarding the adequacy of resources for domestic violence-exposed students. Recommendations suggested by school leaders included more domestic violence specific training for school staff and training delivery methods that were more sensitive for staff who have personal experiences with domestic violence. School leaders expressed great concerns for teachers, particularly less experienced teachers, regarding their knowledge and skills to assist students who disclose family violence.